Phase II study of 24-hour infusion of paclitaxel (Intaxel) with carboplatin in advanced non-small cell lung cancer. - Charoentum C. (2014)
PURPOSE: To determine the activity and toxicity of combined 24-hour infusion of paclitaxel with carboplatin in advanced non-small cell lung cancer. PATIENTS AND METHODS: Eligibility required measurable disease; stage III B with malignant pleural effusion or stage IV disease, with a performance status (PS) of ECOG 0-2. Chemotherapy consisted of 24 hours continuous infusion of paclitaxel at 135 mg/m(2) on day 1, followed by carboplatin (AUC=6) on day 2. Treatment was repeated at 3-week intervals for a total of 6 cycles. RESULTS: Thirty-nine patients were enrolled. Twenty six patients were male and 13 female, with a median age of 57 years (range, 38 to 72). Six patients (15%) had stage III B and 33 (85%) had stage IV. PS 0-1/2 was 67%/33%. A total of 131 cycles was administered and the median number of cycles was 4 (range, 2-6). Grade 3-4 neutropenia, grade 3-4 leukopenia and grade 3 anemia occurred in 3%, 3% and 23%, respectively. One patient (3%) developed febrile neutropenia. Grade 3 diarrhea occurred in 3 patients (8%). Other non-hematologic toxicities were mild including mucositis and skin rash. The overall response rate was 15%. Median survival was 8 months (range 6-9.5 months) and 1-year survival rate was 20%. CONCLUSIONS: The combined 24-hour infusion of paclitaxel (Intaxel) with carboplatin is a feasible and well-tolerated regimen in the treatment of advanced NSCLC patients.